IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI SDN 17 SUNGAI PUGUK KECAMATAN SAMBAS TAHUN PELAJARAN 2023/2204 - Dini Triyuni; Aslan Aslan; Astaman Astaman (ADISAM PUBLISHER, 2025)
This research aims to find out how implementation of merdeka belajar curriculum at SDN 17 Sungai Puguk. This research uses a qualitative approach and a qualitative descriptive research type. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the research show that in planning the learning of the independent learning curriculum at SDN 17 Sungai Puguk there are two main activities carried out, namely the principal and teachers taking part in socialization or training related to the implementation of the independent learning curriculum and preparing teaching modules. The implementation of learning consists of preliminary activities, core activities and closing activities. Evaluation of learning curriculum learning uses two types of assessment, namely formative assessment and summative assessment